Sustainable Development in Asian Countries – Indicator-based Approach - Bartniczak, Bartosz; Raszkowski, Andrzej (Problemy Ekorozwoju, 2019)
The study discusses problems related to the concept of sustainable development in Asian countries in the period 2002-2015. The introduction presents the occurring transformations, involving the majority of Asian countries, taking into account their diversity and contrasts. In addition, the goals allowing the implementation of sustainable development concept in Asia-Pacific region are specified. In the next part of the article the indicators of sustainable development, selected for the analysis and covering all key areas, i.e. social, economic, environmental, spatial, institutional-political are characterised. A synthetic development measure (SDM) was applied as the research method, and the data for calculations were collected from the World Bank sources. The research results, illustrating the position of individual countries against the level of sustainable development concept implementation in the analysed years, remain the crucial part of the study. Within the framework of conclusions it can be stated that the situation of Asian countries, in terms of sustainable development, requires improvement. In turn, a noticeable and gradual progress refers to the majority of analysed countries. The best results were recorded in the following countries: Singapore, Japan, South Korea, Qatar, United Arab Emirates and Malaysia. The least favourable situation was observed in Yemen, Iraq, Burma, Uzbekistan, Cambodia, Oman and Iran.